2014
DOI: 10.1080/10632913.2014.914389
|View full text |Cite
|
Sign up to set email alerts
|

Access to Music Education with Regard to Race in Two Urban Areas

Abstract: This quantitative study examined access to school music instruction with regard to race in two urban areas: Detroit, Michigan, and Washington, DC, in 2009-2010. We found significant differences in the provision of music instruction between schools with high and low proportions of nonwhite enrollment, in categories including curricular offerings, extracurricular offerings, and resources. In the Detroit area, only 31 percent to 60 percent of schools with high percentages of nonwhite students offered any music in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…Factors such as rising income inequality, poverty, unemployment, racism, and xenophobia are common features of our current sociopolitical landscape. Music education scholars have identified ways in which injustices and inequities persist as direct outcomes of either structural barriers, such as inequitable access to music instruction locally (Salvador & Allegood, 2014), which results in unequal participation rates across demographic groups in music classes nationally (Elpus & Abril, 2011; Lorah, Sanders, & Morrison, 2014), or as a direct function of the practices within music classrooms, such as curricula that are irresponsive to students’ cultural backgrounds (Kelly-McHale, 2013). The topic of social justice refers to the awareness of and actions toward correcting injustices and inequities such as these.…”
mentioning
confidence: 99%
“…Factors such as rising income inequality, poverty, unemployment, racism, and xenophobia are common features of our current sociopolitical landscape. Music education scholars have identified ways in which injustices and inequities persist as direct outcomes of either structural barriers, such as inequitable access to music instruction locally (Salvador & Allegood, 2014), which results in unequal participation rates across demographic groups in music classes nationally (Elpus & Abril, 2011; Lorah, Sanders, & Morrison, 2014), or as a direct function of the practices within music classrooms, such as curricula that are irresponsive to students’ cultural backgrounds (Kelly-McHale, 2013). The topic of social justice refers to the awareness of and actions toward correcting injustices and inequities such as these.…”
mentioning
confidence: 99%
“…Regional and local factors can also have an influence on access to secondary music course offerings, especially for marginalized students (Elpus, 2017; Gerrity, 2009; Salvador & Allegood, 2014). For example, Elpus (2017) found 59% of public high schools in the Western United States offered music courses compared with 85% of the public high schools in the Midwest.…”
Section: Structural Factors Related To Secondary Music Participationmentioning
confidence: 99%
“…While the aforementioned research focused on schools that offer music programs, Salvador and Allegood (2014) reported a lack of structural access: Schools with high proportions of non-White students were less likely to offer any music program whatsoever. Focusing on a more cultural aspect of access, Butler, Lind, and McKoy (2007) argued that the existence of a music program in a school does not necessarily mean that all students in the school have equitable access to instruction.…”
Section: Social Justice In Music Educationmentioning
confidence: 99%
“…Researchers have described promising practices (e.g., Abril, 2009;A. R. Hoffman, 2011;Kelly-McHale, 2013;Shaw, 2012), related historical precedents (e.g., Gustafson, 2009), discussed philosophical arguments (e.g., Bowman, 2007;Kindall-Smith, McCoy, & Mills, 2011;Koza, 2008), and revealed demographic trends with regard to music education and race, class, gender, sexual orientation, ability, country of origin, and socioeconomic status (e.g., Elpus & Abril, 2011; E. C. Hoffman, 2011;Salvador & Allegood, 2014). However, in music teacher education (as in general education), researchers have not attempted to ascertain the prevalence or nature of social justice education in music teacher preparation or the extent to which social justice is valued or understood by teacher educators.…”
Section: Purpose and Problemsmentioning
confidence: 99%